Zarządzanie systemami opartymi o sztuczną inteligencję w teorii i praktyce - Urbaniak-Mastalerz, Izabela (Wydawnictwo Politechniki Łódzkiej, 2022)
This study presents the issues of managing systems based on artificial intelligence in theory and in practice based on actual cases. This article indicates selected problems related to the management of such systems based on artificial intelligence in the aspects of copyright, liability and the scope of regulations. The author will attempt to resolve the problem of how to interpret the most important issues related to the management of systems based on artificial intelligence in selected legal aspects. Based on the available statistics, conclusions from the issues discussed, available judgments and decisions of competent authorities in Poland and around the world will be the starting point for making an assessment in this area.
Managing Systems Based on Artificial Intelligence in Theory and in Practice
Keywords: management; artificial intelligence; intellectual property; protection; zarządzanie; sztuczna inteligencja; własność intelektualna; ochrona